Empowerment of farmer groups in development cocoa agribusiness in Soppeng Regency. Issue 1 (April 2020) - Astari, A; Bulkis, Sitti; Kaimuddin,
Abstract: The purpose of this study is to analyze the process of empowering cocoa farmer groups. This study used a qualitative research approach. Sampling in this study was conducted purposively consisting of 50 cocoa farmers. The sample in this study were the cocoa farmers who participated in the empowerment of farmer group program conducted in Soppeng, South Sulawesi province. Data collection techniques are done by using interview, observation and documentation study. Data were analyzed using qualitative descriptive analysis. The results showed that the process of empowering cocoa farmer groups in Soppeng District consisted of the process of empowering cocoa farmer groups in Soppeng Regency includes 3 stages, namely the awareness stage, the organizing stage and the delivery stage. However, the process was not running well.